2011
DOI: 10.1111/j.1524-4725.2011.02032.x
|View full text |Cite
|
Sign up to set email alerts
|

Commentary: Treatment of Cutaneous Lupus Erythematosus Using the Pulsed Dye Laser

Abstract: The authors have indicated no significant interest with commercial supporters.T he prospective study by Truchuelo Díez and colleagues 1 points the way ahead. For the first time, histologic and immunohistologic examinations have been conducted and their results correlated with the similarly excellent clinical results.The treatment of cutaneous lupus erythematosus (CLE) using the pulsed dye laser (PDL) was described for the first time by the group of Pablo Boixeda and Maria Nunez. 2 Since then (15 years ago!), t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…To our knowledge, there have been no reports of the use of lasers in the ultraviolet A or B spectrum, namely, the excimer laser, because wavelengths in these spectrums are known to be photosensitizing in LE, although there have been numerous reports of the use of lasers with wavelengths in the visible light spectrum (PDL, argon, and intense pulsed light (IPL) with a 515‐nm filter), which were relatively well tolerated. These findings may support the hypothesis that monochromatic laser light is unlikely to be photosensitizing in LE and, if administered correctly, may be a safe treatment option in select patients …”
Section: Methodssupporting
confidence: 73%
See 3 more Smart Citations
“…To our knowledge, there have been no reports of the use of lasers in the ultraviolet A or B spectrum, namely, the excimer laser, because wavelengths in these spectrums are known to be photosensitizing in LE, although there have been numerous reports of the use of lasers with wavelengths in the visible light spectrum (PDL, argon, and intense pulsed light (IPL) with a 515‐nm filter), which were relatively well tolerated. These findings may support the hypothesis that monochromatic laser light is unlikely to be photosensitizing in LE and, if administered correctly, may be a safe treatment option in select patients …”
Section: Methodssupporting
confidence: 73%
“…The authors acknowledge the lack of use and reporting of lasers in treatment of LE and that laser medicine is not considered in treatment algorithms despite evidence to support that it is well tolerated and effective. Reasons that Raulin and colleagues proposed for PDL not reaching mainstream therapy for cutaneous LE include lack of awareness or interest on the part of dermatologists with little knowledge or experience with lasers or that those with the experience have a greater interest in the treatment of cosmetic and aesthetic concerns …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 ] Raulin et al . [ 12 ] challenged as to why PDL has not been incorporated into the conventional treatment algorithms in the context of LE and suggested that in part dermatologists may not be aware or appreciate the full use of lasers and therefore do not implement laser therapy in their treatment regimes. We would agree that we anticipated having treated more LE patients in our laser clinic, but it is possible that cases were not referred due to a lack of awareness.…”
Section: Discussionmentioning
confidence: 99%